Philosophical journalism in new media - Maksim V. Yakovlev (RUDN Journal of Studies in Literature and Journalism)
In response to the increasing educational role of the media and the growing public demand for educational materials, the author examines Internet resources dedicated to philosophy, including author channels in instant messengers. The concept of modern philosophical journalism is formulated, the uniqueness of the content of Russian and English-language media positioning themselves within the framework of philosophy is revealed. A conclusion is drawn about their peculiarities in working methods and objectives. A comparative content analysis of the publications of ten media projects revealed two strategic directions in the development of philosophical journalism on screen. The first is educational and entertaining, which tends to fulfill two basic functions of journalism: education and entertainment. The second one is scientific and journalistic, which mainly fulfills the educational and informational functions of the media (to a lesser extent the educational function). The first direction is characterized by the intensive use of multimedia components, a focus on presenting the foundations of teachings and explaining basic philosophical concepts, ignoring the current agenda. The second direction uses information opportunities, in philosophical issues there is a connection with the issues of the current agenda, an emphasis on the development of audio podcasts and longreads. Russian journalists connected with philosophical issues are invited to expand their contribution to the development of philosophical journalism on digital resources, bringing them closer to the standards of high-quality publications and increasing the effectiveness of information and journalistic work.